Extensor indicis proprius to extensor pollicis longus tendon transfer with first dorsal interossei muscle flap cover for reconstruction of post traumatic thumb defect in an acute setting: a very rare case report - Bhat, Tanveer Ahmad; Altamimi, Abdulla S.; Alsharari, Musleh K.; Mirza, Mohammed Y. (International Journal of Research in Medical Sciences, 2023)
The thumb plays a vital role in the function of the hand and is indispensable part of gripping, pinching and other activities and therefore its reconstruction is a priority for every hand surgeon. Different flaps have been used in the soft tissue reconstruction of the thumb. Here we presented a 38 year male patient case of road traffic accident with trauma to the right upper limb having composite tissue defect involving the thumb with loss over the dorsum of the thumb with periosteal stripping and partial loss of the dorsal cortex of the metacarpal in which we have successfully performed thumb reconstruction in acute setting by doing extensor indicis proprius (EIP) to extensor pollicis longus (EPL) tendon transfer for the extensor tendon loss and soft tissue cover by using the ulnar head of first dorsal interossei muscle with overlying split thickness skin graft. EIP to EPL transfer is an efficient tendon transfer to restore the thumb extension in post-traumatic extensor loss of thumb without any functional donor site morbidity. First dorsal interossei muscle is a good and reliable reconstructive option for the small full thickness soft tissue defects over the first metacarpal first because of its axial blood supply. We recommend to divide the extensor indicis proprius tendon around half centimetre proximal to the extensor hood and suture this tendon remnant to the side by extensor digiti communis tendon while maintaining the finger extension and for the first dorsal interossei muscle flap preferably use the ulnar head of muscle for thumb reconstruction to avoid functional donor site morbidities.